Intra-horn Penile Intromission in the Alpaca Vicugna pacos and Consequences to Genital Morphology. (10th May 2021) - Brennan, Patricia L R; Sterett, Maya; DiBuono, Mary; Lara Granados, Genesis; Klo, Kay; Marsden, Rebecca; Schleinig, Pearl; Tanner, Louise; Purdy, Stephen
Synopsis: Copulatory behavior and genital morphology interact to deliver sperm more effectively during mating, but the nature of this interaction has not been explored in depth in most vertebrates. Alpacas have unusually long copulations lasting 15–20 min, and a unique copulatory behavior, where the penis intromits all the way past the cervix, into the uterine horns. Here we describe the morphology of male and female genitalia and report unique morphological characteristics that may be associated with this unusual insemination mode. Vaginal shape is highly variable, and seemingly not associated with age or parity. The cranial vagina varies between bulbous and cylindrical, while the caudal vagina is typically narrower and always cylindrical. The cervix consists of a series of two to three spirals or rings, and it is often found in a relaxed state that may prevent damage caused by the cartilaginous penis tip as it pushes through the cervix to reach the uterine horns. The uterus and uterine horns have a complex shape with multiple constrictions. The cartilaginous penis tip has a sharp urethral process that may help to push against these constrictions. The diameter of the vaginal lumen is much greater than the diameter of the penis suggesting that there is little direct interaction between them, and that female vaginal shape is not under strong copulatory selection. In effect, the entire female reproductive tract of the female is interacting with the penis during copulation.